Whos is It ? - Tim Elex Media Komputindo (Elex Media Komputindo, 2009)
Whose is it? Is a simple way For young children to learn about Follow the adventures of Ladybirdand learn about animal's egg, food, home, best friend, and behavior. Pull the book and find out what inside is.